Formulação peletizada de metarhizium spp.: produção, termotolerância e potencial no controle de rhipicephalus microplus - Paixão, Flávia Regina Santos da (2016)
Rhipicephalus microplus engorged females lay their eggs in shaded and humid areas on the soil; these areas seems favorable for entomopathogenic fungi development, where they could be applied for tick control. This study produced pellets based on microesclerotia (ME) of Metarhizium spp. (CG 47, CG 632, IP 46, IP 119, ARSEF 1883 and ARSEF 2575) and assessed their virulence toward R. microplus engorged females under laboratory conditions. Microsclerotia produced in specific liquid medium were processed for pelletization. Conidial production and viability of conidia from each formulated Metarhizium spp. was evaluated by distributing 0,003 g pellets 2% water-agar medium, and incubating them at 27 °C or 32 °C for 15 days. The results showed that the conidial production among isolates was similar at 27 °C or 32 °C, and the viability of the conidia was superior than 90% for conidia produced. Two bioassays were conducted for screening the virulence of isolates against R. microplus: the first one tested 0,007 g of pellets of each Metarhizium spp. isolate; the second one tested different concentrations of IP 119 pellets (0,002, to 0,006 g). Pellets were sprinkled on the surface of 5 g sterile oxisol in Petri dishes, moistened with 2 ml sterile-distilled water. Ten replicates were prepared for each fungal isolate. The plates with pellets were incubated for 15 days at 27 °C and RH > 90% to induce conidial production; plates from control groups did not receive pellets. A female was placed in each plate and monitored daily for 15 days for fungal conidiogenesis on ticks. At day 15, the egg mass was removed from each plate and transferred to a glass vial and incubated at 27 ± 1ºC to quantify the number of hatching larvae hatched. In both bioassays the fungal treatment reduced the oviposition period of females, as well as the number of hatching larvae. A bioassay was conducted with IP 47 and IP 119 at two different temperatures: 27 °C or 32 °C. CG 47 pellets incubated at 27 °C incited conidiogenesis on R. microplus females by day 5, whereas IP 119 iniciated conidiogenesis by day 9. Trials conducted at 32 C revealed conidiogenesis on R. microplus females between day 5 and 6 for both fungi. The number of larvae from females exposed to pellets of CG 47 and IP 119 was reduced.. Tests with pellets of ME produced with the different inert materials showed that pellets with vermiculite presented higher conidial production compared with the pellets prepared with cellulose. Therefore, these results together indicate that the pelletized formulation of ME of Metarhizium spp. was effective in controlling R. microplus under laboratory conditions by reducing the number of offspring. This formulation is a potential mycoacaricide, since the temperature and humidity conditions required for production of infective conidia are conducive to those required by this tick to lay eggsand hatching larva in the environment.